Pelatihan dan Pendampingan Media Pembelajaran Interaktif Berbasis Multimedia bagi Guru TK-KB Taman Sari Kabupaten Bayuasin - Nia Oktaviani; Febriyanti Panjaitan; Siti Sauda; Irwansyah Irwansyah; Edi Supratman (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Community Service activities aim to provide skills to partners in developing interactive multimedia-based learning materials. The method used is the approach method which includes observation, interview and counseling. The implementation of this activity was carried out in two meetings or about two days, where the meeting was in the form of presentation of material, and continued with assistance in making multimedia-based learning materials until completion. The results obtained by participants can create interactive learning media with the Sothink SWF Easy application. The response results from participants gave positive statements.